Doksa Penerbit Kristal Multimedia dalam Menerbitkan Ulang Buku-Buku Kaba - Nur Ahmad Salman Herbowo; Khairil Anwar; Ferdinal Ferdinal (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2021)
The republishing activities of Kaba books carried out by the publisher Kristal Multimedia cannot be separated from the publisher Pustaka Indonesia, one of the earliest publishers managed by local communities in Bukittinggi during the Dutch colonial administration. Sixteen of the eighteen Kaba books that were printed were republished from the publisher Pustaka Indonesia. This research uses the republishing of Kaba books by Kristal Multimedia publisher as its material object. The formal object is doxa which the publisher of Kristal Multimedia expresses. The purpose of this study is to determine the background that causes the publishers of Kristal Multimedia to continue operating and is serious about republishing Kaba books. The research method used is qualitative research methods with interview data collection techniques and the use of documents. The theory used in this research is the arena of cultural production proposed by Pierre Bourdieu, focus the discussion of doxa, heterodoxa and orthodoxa. Doxa expressed by Kristal Multimedia publisher is heterodoxa, contradicting the doksa expressed by the publisher Pustaka Indonesia as a publisher that also produces school and religious textbooks. Kristal Multimedia Publisher focuses on all its publications in Minangkabau cultural books, such as the Kaba book.